505 Linear Growth in Children with Congenital Acyanotic Heart Disease (Chd) before Versus after Surgical Intervention. (October 2012) - Soliman, A; Yassin, H; Saeed, S; Khellah, A; Elalaily, R; Elawwa, A
Abstract : Objectives: To evaluate linear growth and insulin-like growth factor- I (IGF-I) concentration of patients with congenital acyanotic heart disease (CHD) before versus after surgical intervention. Design: 27 infants and children with CHD (10 with VSD, 8 with ASD, 9 PDA) without heart failure, before and 12 months or more after surgical or catheter intervention. Eighty normal children served as controls. Results: At presentation, age = (35.6 +/– 26 months), patients were significantly shorter, height SDS (HtSDS)(−1.6 +/– 1.1) and had lower BMI (15.1 +/– 2.5) compared to normal controls (HtSDS = 0.25 +/– 0.3, BMI = (16.4 +/– 1.5). One year or more after catheter or surgical treatment the HtSDS and BMI increased significantly in patients to –0.55 +/– 0.9 and 15.9 +/– 1.5 respectively. Circulating concentrations of IGF-I increased from 46.8 +/– 29 mcg/L before to 77.3 +/– 47.6 mcg/L after intervention. The HtSDS after treatment was correlated with the IGF-I concentration (r = 0.804, P<0.001). The change in the HtSDS after intervention was correlated significantly with BMI (r=0.594, p<0.001). The shunt size was correlated negatively with BMI before intervention (r = - 0.35, P<0.01) and with HtSDS (r = –0.461, p<0.05). Conclusions: These data denoted that early surgical interference and good weight gain have beneficial effect on postoperative growth spurt. The accelerated linear growth after intervention appears to be mediated through activation of the GH/IGF-I system.